Adolescents' Knowledge and Attitudes Toward Reproductive Health Using Website and Booklet Media - Seri Wahyuni; Wahidah Sukriani; Apriantoro, Nursama Heru (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Sexuality is considered a taboo topic by society, making it difficult to discuss openly. Parents typically provide minimal guidance, while teenagers frequently feel too embarrassed to ask questions. To overcome these barriers, a more engaging and accessible platform, such as a website dedicated to reproductive health, is necessary to help teenagers gain a better understanding of the topic. This study aims to analyze the influence of reproductive health education through website media on changes in adolescent knowledge and attitudes. This research is a quasi-experiment, a quantitative study. The research was conducted from March to November 2024. The respondents/subjects were 200 teenagers aged 15-18 years in Palangka Raya who owned a smartphone or laptop. The intervention group had an average knowledge score of 22.90, higher than the control group's score of 20.49. The Independent T-test showed a significance value of 0.000 (<0.05), indicating that education using the booklet was less effective in increasing knowledge compared to the website+booklet. Similarly, the intervention group's average attitude score was 127.67, higher than the control group's score of 122.08. The Independent T-test showed a significance value of 0.000 (<0.05), indicating that using only the booklet was less effective in improving attitudes compared to the combined website+booklet approach. Education on reproductive health delivered through a website and booklet is more effective at enhancing knowledge and attitude scores in adolescents than education provided solely through a booklet. Ensure that the digital platform is accessible to all adolescents, including those in remote areas.